31P magnetic resonance fingerprinting for rapid quantification of creatine kinase reaction rate in vivo. (15th September 2017) - Wang, Charlie Y.; Liu, Yuchi; Huang, Shuying; Griswold, Mark A.; Seiberlich, Nicole; Yu, Xin
Abstract : The purpose of this work was to develop a 31 P spectroscopic magnetic resonance fingerprinting (MRF) method for fast quantification of the chemical exchange rate between phosphocreatine (PCr) and adenosine triphosphate (ATP) via creatine kinase (CK). A 31 P MRF sequence (CK‐MRF) was developed to quantify the forward rate constant of ATP synthesis via CK ( k f CK ), the T 1 relaxation time of PCr ( T 1 PCr ), and the PCr‐to‐ATP concentration ratio ( M R PCr ) . The CK‐MRF sequence used a balanced steady‐state free precession (bSSFP)‐type excitation with ramped flip angles and a unique saturation scheme sensitive to the exchange between PCr and γATP. Parameter estimation was accomplished by matching the acquired signals to a dictionary generated using the Bloch‐McConnell equation. Simulation studies were performed to examine the susceptibility of the CK‐MRF method to several potential error sources. The accuracy of nonlocalized CK‐MRF measurements before and after an ischemia–reperfusion (IR) protocol was compared with the magnetization transfer (MT‐MRS) method in rat hindlimb at 9.4 T ( n  = 14). The reproducibility of CK‐MRF was also assessed by comparing CK‐MRF measurements with both MT‐MRS ( n  = 17) and four angle saturation transfer (FAST) ( n  = 7). Simulation results showed that CK‐MRF quantification of k f CK was robust, with less than 5% error in the presence of model inaccuracies including dictionary resolution, metabolite T 2 values, inorganic phosphate metabolism, and B 1 miscalibration. Estimation of k f CK by CK‐MRF (0.38 ± 0.02 s −1 at baseline and 0.42 ± 0.03 s −1 post‐IR) showed strong agreement with MT‐MRS (0.39 ± 0.03 s −1 at baseline and 0.44 ± 0.04 s −1 post‐IR). k f CK estimation was also similar between CK‐MRF and FAST (0.38 ± 0.02 s −1 for CK‐MRF and 0.38 ± 0.11 s −1 for FAST). The coefficient of variation from 20 s CK‐MRF quantification of k f CK was 42% of that by 150 s MT‐MRS acquisition and was 12% of that by 20 s FAST acquisition. This study demonstrates the potential of a 31 P spectroscopic MRF framework for rapid, accurate and reproducible quantification of chemical exchange rate of CK in vivo . Abstract : A 31 P spectroscopic pulse sequence based on a magnetic resonance fingerprinting framework was designed to quantify the forward rate constant of ATP synthesis via creatine kinase. Simulation results demonstrated the robustness of this method to several sources of experimental errors. In vivo studies on rat hindlimb showed significantly higher reproducibility than the conventional magnetization transfer method with only 13% of the acquisition time.